STRATEGIES IN COPING WITH PSYCHOLOGICAL STRESS IN FOREIGN LANGUAGE ACQUISITION OF STUDENTS MAJORING IN PEDAGOGY, UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES – VIETNAM NATIONAL UNIVERSITY, HANOI - Lan, Dang Thi (VNU Journal of Foreign Studies, 2019)
Changes in training methods from fixed - curriculum system to credit system with teaching methods towards creative and innovation thinking and entrepreneur using advanced technology… has put students at the University of Languages and International Studies - Vietnam National University Hanoi in difficulty, and at risk of psycholgical stress in learning activities. When students encounter psycholgical stress without strategies to overcome, their academic performances will be severely influenced. The research aims to clarify the effectiveness of strategies to cope with psychological stress in foreign language acquisition of students at the University of Languages and International Studies. By using a system of research methodologies, the researcher clarified the theoretical and practical foundation of the strategies in coping with psychological stress in foreign languages acquisition of the students. Research results showed that students encoutered heavily psychological stress in terms of cognitive and behaviour rather than physiology and emotion; the level of psychological stress in foreign language acquisition of experimental group students was minimized due to the influence of impact measures. Its minimization was more than that of control group students. This finding allows to affirm that Instructing students to adjust their cognitive in foreign language acquisition is an appropriate and effective strategy to minimize psychological stress in foreign language acquisition of students majoring in pedagogy, the University of Langugaes and International Studies - Vietnam National University Hanoi.